Pendampingan Penggunaan MYOB Accounting sebagai Persiapan Kompetensi Kerja bagi Siswa SMK Mandiri Palembang - Mutiara Lusiana Annisa (PT. Altaf Publishing Corp, 2025)
The purpose of this community service program is to enhance the ability of SMK Mandiri Palembang students in utilizing MYOB Accounting software as preparation for entering the workforce. Additionally, this program aims to assist teachers in effectively teaching accounting applications, enabling consistent and efficient classroom instruction. MYOB Accounting was selected due to its alignment with the requirements of the accounting and finance sector. The implementation of this program involves training sessions and mentoring activities, specifically designed for students in the Accounting department at SMK Mandiri Palembang. This method is deemed suitable for implementation at SMK Mandiri Palembang. It involves providing training and mentoring focused on introducing MYOB Accounting. The program begins with foundational knowledge about MYOB Accounting, its applications in the field of accounting, and the advantages of mastering this software. The material includes the objectives of using MYOB and highlights key features frequently utilized in business settings. Additionally, the program incorporates case-based simulations to enable students to apply their MYOB knowledge in practical scenarios. These activities include recording initial transactions, generating financial reports, and performing financial analysis. The results indicate that the program was implemented successfully, highlighting the importance of SMK Mandiri Palembang students mastering the technical skills required to operate widely used accounting software, specifically MYOB Accounting. Proficiency in this software is expected to boost students' confidence as they transition into the workforce. Based on the feedback collected from 20 training participants via a questionnaire, the majority responded with